The Human Capital Cost of Radiation: Long-run Evidence from Exposure outside the Womb - Benjamin Elsner; Florian Wozny (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2019)
This paper studies the long-term effect of radiation on cognitive skills. We use regional variation in nuclear fallout caused by the Chernobyl disaster in 1986, which led to a permanent increase in radiation levels in most of Europe. To identify a causal effect, we exploit the fact that the degree of soil contamination depended on rainfall within a critical ten-day window after the disaster. Based on unique geo-coded survey data from Germany, we show that people who lived in highlycontaminated areas in 1986 perform significantly worse in standardized cognitive tests 25 years later. This effect is driven by the older cohorts in our sample (born before 1976), whereas we find no effect for people who were first exposed during early childhood. These results are consistent with radiation accelerating cognitive decline during older ages. Moreover, they suggest that radiation has negative effects even when people are first exposed as adults, and point to significant external costs of man-made sources of radiation.
Keywords: J24; Q53; 330; Environment; Human Capital; Radioactivity; Cognitive Skills